Negotiating Trade in Services with China from the Uruguayan Perspective - Bartesaghi, Ignacio; Gari, Gabriel; Melgar, Natalia (Latin American Journal of Trade Policy, 2021)
We focus on trade in services, and we aim at assessing the concessions made by China when negotiating trade agreements. Additionally, we shed light on the opportunities that Uruguay may have in exporting services to China in case of signing a Free Trade Agreement (FTA). The debate on this issue started in 2016 when Uruguayan President Vázquez visited China and with Chinese President Xi Jinping raised the possibility of signing a FTA. Since then, opposing arguments have been put forward. Unfortunately, the lack of bilateral information on trade in services is a limitation for this kind of studies. It is highlighted that there will be additional large gains which would emerge from trade in goods, cooperation or investments.